Response of Growth and Results of Sweet Corn Plants (Zea mays Saccharata Sturt.) To the Effect of Dosage and Time of Fertilizing Bio-slurry Liquid Fertilizers - Oktavia, Vina; Pujisiswanto, Hidayat; Edy, Akari; Andalasari, Tri Dewi (Politeknik Negeri Lampung., 2018)
The study aimed to was determine the effect of dose and time of fertilization bio-slurry liquid fertilizer on the growth and yield of sweet corn was held in Tanjung Laut, Fajar Baru village, Jati Agung district, South Lampung regency in October 2016 to January 2017. In this study used Randomized Block Design (RBD) with factorial treatment design (4 x 2) with three replications. The first factor was the dose of bio-slurry liquid fertilizer consisted 4 levels were 0, 25, 50, and 75 l/ha. The second factor was the fertilization time consisted of 2 levels were (2 and 4 MST) and (2, 4, and 6 MST). Variance of homogeneity was tested by Bartlett's test, if the assumptions were met, the data were analyzed by variance using F-test. The difference of median value of treatment will be tested by the Least Significance Difference Test (LSD) at 5% level. The results showed that the treatment of several doses of bio-slurry liquid fertilizer has an effect on the length of cob, while the treatment of some fertilization time has an effect on dry weight variables. However, the treatment of some dose levels and fertilization time of bio-slurry liquid fertilizer has not been able to increase growth and yield. Proper fertilization time does not depend on the dose of bio-slurry liquid fertilizer given in influencing the growth and yield of sweet corn crops.